An attempt to improve the immunization of sheep against heart-water by using different combinations of 3 stocks of Cowdria ruminantium - du Plessis, J L; Potgieter, F T; van Gas, L (Onderstepoort journal of veterinary research, 1990)
Neither sheep immune to the Ball 3, the Kwanyanga or the Mara stocks of Cowdria ruminantium nor those immunized with combinations of these 3 stocks were protected against challenge with the Mali stock. Against challenge with the Welgevonden stock, however, immunization with each of the 3 combinations and with single stocks effected a protective immunity.